New combinations and typification in Shivparvatia (Alsineae, Caryophyllaceae) - Rabeler, Richard K. (Phytotaxa, 2017)
Four new combinations in Shivparvatia (Alsineae, Caryophyllaceae) are made to accommodate placement of all currently recognized taxa of Arenaria subg. Solitariae within the genus Shivparvatia.